Copolymerization of nadic anhydride with styrene: Reactivity ratios. (15th February 2021) - Jeemol, Poovathungal Abdulrahman; Mathew, Suresh; Nair, Chethrappilly Padmanabhan Reghunadhan
Abstract : The free radical copolymerization of nadic anhydride (NA) and styrene (St) at 80°C has been investigated for the first time. The copolymerization was done in toluene using benzoyl peroxide as initiator. The monomer reactivity ratios were calculated from the copolymer composition (estimated from the acid value) by using Fineman–Ross, Kelen–Tüdös, and Extended Kelen–Tüdös methods. The reactivity ratios (rNA, = 0.34, rST = 0.84) implied a good copolymerizability for the monomer pair and existence of an azeotropic composition at fNA = 0.195. The unsaturation in nadic anhydride exhibited good copolymerizability despite the fact that the double bond is isolated and allylic in nature. The usual retardation by the allylic protons was not significantly felt in this case, as the allylic protons were located at a bridge head posing geometric restrictions for stabilization of the allylic free radicals. However, an increase in concentration of NA in the feed decreased the overall rate of copolymerization. Based on the reactivity ratio, the probability for formation of sequences of NA in its copolymer with styrene was computed for a few compositions.